Congruence between preferred and actual place of death and its association with quality of death and dying in advanced cancer patients: A nationwide survey in Japan. - Mariko Shutoh; Tatsuya Morita; Maho Aoyama; Yoshiyuki Kizawa; Yasuo Shima; Mitsunori Miyashita (PLoS ONE)
Background Satisfying patients' preferences is an important outcome in palliative care. Previous research has reported that a patient's place of death was associated with quality of death and dying. Purpose This study aimed to evaluate the association between the congruence between a patient's preferred and actual place of death and their quality of death and dying, as perceived by their family caregivers. Method Data were obtained from a nationwide cross-sectional questionnaire survey of bereaved family caregivers of patients with cancer in Japan. A total of 13,711 family caregivers participated. We evaluated the quality of death and dying using the Good Death Inventory. Results 9,123 responses were analyzed (effective response rate: 67%). Patients who died in their preferred place were categorized as the "achieved group," whereas patients who died in a place that they did not prefer were classified as the "not-achieved group." Good Death Inventory scores were significantly higher for the achieved group compared with the not-achieved group (48.8 ± 10.1 and 44.0 ± 9.5, respectively; p < 0.001). A multiple linear regression analysis indicated that congruence between the preferred and actual place of death was an independent determinant of good quality of death and dying (p < 0.001). Conclusion Congruence between a patient's preferred and actual place of death may contribute to better quality of death and dying among terminally ill patients with cancer. Congruence between the preferred and actual place of death should be regarded as an essential component in end-of-life care.